2013
DOI: 10.1590/s1516-35982013000500007
|View full text |Cite
|
Sign up to set email alerts
|

Mineral requirements for growth of wool and hair lambs

Abstract: The present study was conducted to determine the body composition and the mineral requirements for growth of wool and hair lambs. A total of 34 castrated lambs with an initial body weight (BW) of 19.9±0.8 kg were used; 17 of these lambs were of the genotype Ideal × Ile de France and 17 were Santa Inês. Ten lambs (5 of each genotype) were slaughtered at the beginning of the experiment to establish their initial body composition. The remaining lambs were assigned to one of three diets (40% roughage and 60% conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Factors such as age, physiological stage and genotype affect the mineral demands of animals. The different genotypes are known to exhibit differences in body composition and metabolism (Teixeira et al, 2013). The particularities of the genotypes have been rarely considered in studies on nutritional demands, especially regarding the mineral needs of small ruminants (NRC, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as age, physiological stage and genotype affect the mineral demands of animals. The different genotypes are known to exhibit differences in body composition and metabolism (Teixeira et al, 2013). The particularities of the genotypes have been rarely considered in studies on nutritional demands, especially regarding the mineral needs of small ruminants (NRC, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mineral requirements are also affected by the genotype of the animals (Teixeira et al, 2013), but in the literature do not exist reports comparing dairy goat breeds. The world's largest dairy herd consists of the Saanen breed, and in some countries Oberhasli goats are among the main breeds in their dairy goats herd (Irano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that when the Zn, Fe, Cu, and Co contents were expressed based on the metabolic weight (mg/kg 0.75 of EBW) (Table 3), a linear increase was observed in response to the increased level of supplementation. This concentration pattern may have been a reflection of the increased mineral intake and weight gain, which led to a better body development of the animals as the increase in BW has been noted as one of the main discriminating factors in body composition (Mahgoub and Lu, 1998;Bellof and Pallauf, 2007;Fernandes et al, 2007;Araújo et al, 2010;Fernandes et al, 2012;Teixeira et al, 2013). Silva et al (2013) observed that trace element concentrations in the empty body of Canindé goats increased as feed intake levels increased.…”
Section: Discussionmentioning
confidence: 92%
“…These findings indicate that the manganese net requirements for growth are higher in goats than in sheep. Animals of different genotypes are well known to exhibit differences in their mineral requirements due to the differences in their body composition (Teixeira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as gender, genotype, age, and physiological state influence the animals' mineral requirements (Bellof et al 2006;Bellof and Pallauf,. 2007;Fernandes et al 2012;Teixeira et al 2013), because lambs in various situations may have different body composition , and at the same time the mineral distribution changes depending on the tissue type (Bellof et al 2006;Ji et al 2012), but such differences in requirements have rarely been considered in studies. Chizzotti et al (2009) reported no differences in the net requirements for growth of all macrominerals among genders in bulls, steers, and heifers of Nellore and Red Angus crossbreds, and feeding systems for sheep including the recommended mineral requirements are also independent of the genotype and gender (ARC 1980;NRC 2007;CSIRO, 2007;Suttle, 2010).…”
Section: Net Mineral Requirements For Growthmentioning
confidence: 99%